(untitled) (American Journal of Islam and Society, 2002)
The book under review offers a monumental, exhaustive and judicious account of"who are the agents behind the ’horrendous violence’ that has followed the consolidation of the military over incumbent authorities?" The answer provided by the victors, those with the power to institute their choic es and interpretations, is that the paroxysm of "Islamic fundamentalism" is exacting grisly, gratuitous and ghastly violence on a society they have been unable to conquer. On the contrary, scholars insist the beneficiaries of the resource rich regions of Algeria, largely unscathed in the carnage, are indicative of the faceless murderers behind the monstrosity. Moreover, the primary importance of these resources to foreign states and corporations indicates complicity. Amidst this confusing scenario, An lnqui!J’ into the Algerian Massacres provides a clear analysis of the beastly culprits. Major international human rights organizations and outstanding journalists have not found the "Islamic fundamentalist" argument compelling and continue to raise the same question: "Who is behind these grisly atrocities?" The evidence unearthed strongly suggests that the unseen hands, responsible for the bloodbath, belong to the Algerian army. In addition, striking corroboration has come from defectors and victims which incriminates the Algerian military apparatus and such foreign co-conspirators as the French government. This allegation is firmly supported by the environs of the savagery, taking place in close proximity to military and police installations, yet raging for long periods with no interference. Further disturbing, this charge against the Algerian authorities becomes increasingly credible against the backdrop of the hideous record of rape, torture and mutilation perpetrated by Algerian mjlitary authorities, well documented by independent human rights monitors and reputable reporters. Noam Chomsky, in his insightful foreword to the book, collaborates this ...